2013
DOI: 10.1016/j.celrep.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Human Stem Cell-Derived Spinal Cord Astrocytes with Defined Mature or Reactive Phenotypes

Abstract: SUMMARY Differentiation of astrocytes from human stem cells has significant potential for analyzing their role in normal brain function and disease, but existing protocols generate only immature astrocytes. Using early neuralization, we generated spinal cord astrocytes from mouse or human embryonic (ESCs) or induced pluripotent (hiPSCs) stem cells with high efficiency. Remarkably, short exposure to FGF1 or FGF2 was sufficient to direct these astrocytes selectively toward a mature quiescent phenotype, as judged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
281
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(301 citation statements)
references
References 104 publications
20
281
0
Order By: Relevance
“…Specifically, with respect to GFAP, previous studies have shown heterogeneity in both maturity and marker expression in cultures of human stem cell-derived astrocytes, but identify GFAP expression as a marker for astroglial identity (90), and GFAP is commonly used to characterize astroglial differentiation in hNSC cultures (91)(92)(93). Critically, more mature astroglial markers such as GLAST and ALDH1L1 are absent in human cell cultures ,4 wk old (90).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, with respect to GFAP, previous studies have shown heterogeneity in both maturity and marker expression in cultures of human stem cell-derived astrocytes, but identify GFAP expression as a marker for astroglial identity (90), and GFAP is commonly used to characterize astroglial differentiation in hNSC cultures (91)(92)(93). Critically, more mature astroglial markers such as GLAST and ALDH1L1 are absent in human cell cultures ,4 wk old (90).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, with respect to GFAP, previous studies have shown heterogeneity in both maturity and marker expression in cultures of human stem cell-derived astrocytes, but identify GFAP expression as a marker for astroglial identity (90), and GFAP is commonly used to characterize astroglial differentiation in hNSC cultures (91)(92)(93). Critically, more mature astroglial markers such as GLAST and ALDH1L1 are absent in human cell cultures ,4 wk old (90). Additionally, our data are consistent with previous studies demonstrating the progressive loss of Nestin in NSC during differentiation in vitro, and the progressive upregulation of GFAP in a subpopulation of NSC that differentiate into astrocytes (94,95).…”
Section: Discussionmentioning
confidence: 99%
“…While the treatment of immature astrocytes with FGF1 or FGF2 promoted up-regulation of maturation markers such as glutamate transporters and downregulation of GFAP, treatment with tumor necrosis factor-pushed cells toward a reactive astrocyte phenotype. These cells can be used to model human pathological processes in vitro and in vivo as well as for therapeutic transplantation [163] . More recently the Zhang laboratory reported another shorter duration protocol for generating astrocytes from iPSCs by differentiation of these cells into neuroepithelial cells, followed by removal of mitogen and treatment with CNTF to induce differentiation into astrocytes [70] .…”
mentioning
confidence: 99%
“…Not only is the availability of such samples limited, but they also represent the end-stage of the disease only, hence potentially propagating the toxicity of an inflamed spinal cord environment. It is also argued that astrocytes produced from post-mortem tissue-derived neural precursors are immature and thus do not fully reproduce normal cell function (53). Therefore, the development of iPSC technology allowed for these challenges to be overcome and offered an opportunity to conduct in vitro investigations into different genetic subtypes of ALS.…”
Section: Human Astrocytesmentioning
confidence: 99%
“…Moreover, further differentiation of iPSC-derived neural progenitors into astrocytes can take further 6-8 weeks, with neuronal contamination remaining an issue for a considerable period of the process, though eventually faltering at 2% or less (53,54). The breakthrough in the field of cell reprogramming in ALS research came with the development of a novel protocol for fibroblast reprogramming, which utilises the same defined factors as iPSC technology and manages to bypass the iPSC stage by converting fibroblast directly into induced neural progenitor cells (iNPCs) (17).…”
Section: Human Astrocytesmentioning
confidence: 99%